2022
DOI: 10.2196/22544
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Polio Geographic Information System Platforms in the African Region for Mitigating COVID-19 Contact Tracing and Surveillance Challenges: Viewpoint

Abstract: Background The ongoing COVID-19 pandemic in Africa is an urgent public health crisis. Estimated models projected over 150,000 deaths and 4,600,000 hospitalizations in the first year of the disease in the absence of adequate interventions. Therefore, electronic contact tracing and surveillance have critical roles in decreasing COVID-19 transmission; yet, if not conducted properly, these methods can rapidly become a bottleneck for synchronized data collection, case detection, and case management. Whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The studies that used a map-style representation (79/114) adopted different strategies: static geographic 2D or 3D maps [14,15,19,20,22,31,33,36,38,[42][43][44]50,75,81,83,88,93,102,104,107,109,117,118,123], dynamic 2D maps [20][21][22]25,61,65,80,85,89,90,94,97], or choropleth maps [17,23,24,27,30,32,34,35,37,40,46,48,49,52,…”
Section: Q2: Which Techniques Are Most Frequently Used To Visualize E...mentioning
confidence: 99%
“…The studies that used a map-style representation (79/114) adopted different strategies: static geographic 2D or 3D maps [14,15,19,20,22,31,33,36,38,[42][43][44]50,75,81,83,88,93,102,104,107,109,117,118,123], dynamic 2D maps [20][21][22]25,61,65,80,85,89,90,94,97], or choropleth maps [17,23,24,27,30,32,34,35,37,40,46,48,49,52,…”
Section: Q2: Which Techniques Are Most Frequently Used To Visualize E...mentioning
confidence: 99%
“…Thus, it is easier to understand the data and to draw more assertive strategies. 2,4 Among other advantages, the program features case mapping, real-time information sharing, and remote working options 9 . Power BI can be useful in scientific communication by facilitating the visualization of data in scientific journals.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…The "COVID-19 Panel", widely viewed since 2020, is based on this tool and allowed managers agility in combating the disease and optimizing resources. 9,10 A disadvantage of Power BI is the difficulty of programming the databases. However, training, even virtual training, can solve this issue.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…According to literature review, it was found that GIS was used to develop applications to visualize the number of COVID-19 patients in each region or area [21], [22], [23], [24], mostly visualized in dashboard, consisting of map, statistics, diagram, and spread of COVID-19 in different areas [28]. The data from this research could be used for treatment management in each area for further preparedness of public health.…”
Section: Applying Gis To Covid-19mentioning
confidence: 99%
“…Donators do not have any information to support their decision making on what to donate and how many because the extent of need in each area remains unknown. According to previous studies and literature review, it was found that the current development of geospatial platform for COVID-19 is mostly surveillance and monitoring of the situation in each area [21], [22], [23], [24], including analysis to predict COVID-19 risk [25], [26], [27]. However, geospatial platform for donation management has not been developed yet.…”
Section: Introductionmentioning
confidence: 99%